2012
DOI: 10.1158/1055-9965.epi-12-0803
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Use of Folic Acid and Other Supplements and Risk of Childhood Brain Tumors

Abstract: Background: Interest in a possible protective effect of maternal vitamin use before or during pregnancy against childhood brain tumors (CBT) and other childhood cancers has grown over the past decade. Our Australian study of CBTs, conducted between 2005 and 2011, investigated whether maternal use folic acid and other supplements was protective.Methods: Case children were identified through the 10 Australian pediatric oncology centers and controls were recruited by national random digit dialing. Mothers of 327 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 37 publications
5
84
3
Order By: Relevance
“…Among the studies, one considered folate supplements only [31] and 2 considered dietary folate intake only [29,30], while the other 7 studies considered both folate supplements and dietary folate intake [32][33][34][35][36][37][38]. Five studies reported maternal folate intake during pregnancy only [29-31, 34, 37], whereas the other 5 studies presented findings for maternal folate intake before and during pregnancy separately [32,33,35,36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the studies, one considered folate supplements only [31] and 2 considered dietary folate intake only [29,30], while the other 7 studies considered both folate supplements and dietary folate intake [32][33][34][35][36][37][38]. Five studies reported maternal folate intake during pregnancy only [29-31, 34, 37], whereas the other 5 studies presented findings for maternal folate intake before and during pregnancy separately [32,33,35,36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies reported maternal folate intake during pregnancy only [29-31, 34, 37], whereas the other 5 studies presented findings for maternal folate intake before and during pregnancy separately [32,33,35,36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed recruitment and participation rates have been published previously (1). Briefly, we were notified of 730 eligible CBT cases diagnosed from 2005 to 2010, of whom 568 (77.8%) were invited to participate by their treating clinician.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor subtype analyses were conducted using models as above, limiting cases to specific subtypes compared with all controls. Maternal folic acid supplementation in the month before pregnancy was stratified by genotype; this period of use was most associated with reduced CBT risk in our previous work (1). Evidence for an interaction was assessed formally by fitting a product term to a model (Wald test P values of interaction terms are reported in tables).…”
Section: Genotypingmentioning
confidence: 99%